Data-adaptive image-denoising for detecting and quantifying nanoparticle entry in mucosal tissues through intravital 2-photon microscopy - Bölke, Torsten; Krapf, Lisa; Orzekowsky-Schroeder, Regina; Vossmeyer, Tobias; Dimitrijevic, Jelena; Weller, Horst; Schüth, Anna; Klinger, Antje; Hüttmann, Gereon; Gebert, Andreas (Beilstein Journal of Nanotechnology, 2014)
Intravital 2-photon microscopy of mucosal membranes across which nanoparticles enter the organism typically generates noisy images. Because the noise results from the random statistics of only very few photons detected per pixel, it cannot be avoided by technical means. Fluorescent nanoparticles contained in the tissue may be represented by a few bright pixels which closely resemble the noise structure. We here present a data-adaptive method for digital denoising of datasets obtained by 2-photon microscopy. The algorithm exploits both local and non-local redundancy of the underlying ground-truth signal to reduce noise. Our approach automatically adapts the strength of noise suppression in a data-adaptive way by using a Bayesian network. The results show that the specific adaption to both signal and noise characteristics improves the preservation of fine structures such as nanoparticles while less artefacts were produced as compared to reference algorithms. Our method is applicable to other imaging modalities as well, provided the specific noise characteristics are known and taken into account.
Keywords: 2-photon microscopy (2PM); denoising; in vivo imaging; nanoparticles; signal to noise ratio (SNR); quantum dots

(untitled) - Klinger, A.; Orzekowsky-Schroeder, R.; von Smolinski, D.; Blessenohl, M.; Schueth, A.; Koop, N.; Huettmann, G.; Gebert, A. (Histochem. Cell Biol., 2012)

(untitled) - Qian, S. E.; Lévesque, J. (Opt. Eng. (Bellingham, WA, U. S.), 2009)

(untitled) - Gardner, M. K.; Sprague, B. L.; Pearson, C. G.; Cosgrove, B. D.; Bicek, A. D.; Bloom, K.; Salmon, E. D.; Odde, D. J. (Cell. Mol. Bioeng., 2010)

Proceedings of the International Conference on Networking and Information Technology - Kaur, A.; Kumar, P.; Kumar, P. (Effect of noise on the performance of clustering techniques, Manila, Philippines, 11.6.2010-12.6.2010, 2010)

(untitled) - Rudin, L. I.; Osher, S.; Fatemi, E. (Physica D, 1992)

(untitled) - Murtagh, F.; Starck, J. L.; Bijaoui, A. (Astron. Astrophys., Suppl. Ser., 1995)

(untitled) - Starck, J. L.; Murtagh, F. (IEEE Signal Process. Mag., 2001)

Computer Vision and Mathematical Methods in Medical and Biomedical Image Analysis - Lecture notes in computer science - Demirkaya, O. (Smoothing impulsive noise using nonlinear diffusion filtering, 2004)

Proceedings of the 1st international conference on scale space and variational methods in computer vision - Kervrann, C.; Boulanger, J.; Coupé, P. (Bayesian non-local means filter image redundancy and adaptive dictionaries for noise removal, 2007)

(untitled) - Luisier, F.; Blu, T.; Unser, M. (IEEE Trans. Image Process., 2011)

(untitled) - Boulanger, J.; Kervrann, C.; Bouthemy, P.; Elbau, P.; Sibarita, J. B.; Salamero, J. (IEEE Trans. Med. Imaging, 2010)

(untitled) - Luisier, F.; Vonesch, C.; Blu, T.; Unser, M. (Signal Process., 2010)

(untitled) - Makitalo, M.; Foi, A. (IEEE Trans. Image Process., 2011)

(untitled) - Le Pogam, A.; Hanzouli, H.; Hatt, M.; Le Cheze Rest, C.; Visvikis, D. (Med. Image Anal., 2013)

(untitled) - Dabov, K.; Foi, A.; Katkovnik, V.; Egiazarian, K. (IEEE Trans. Image Process., 2007)

(untitled) - Katkovnik, V.; Foi, A.; Egiazarian, K.; Astola, J. (Int. J. Comput. Vision, 2010)

Conference on Computer Vision and Pattern Recognition - Levin, A.; Nadler, B. (Natural image denoising: Optimality and inherent bounds, Providence, RI, 20.6.2011-25.6.2011, 2011)

(untitled) - Milanfar, P. (IEEE Signal Process. Mag., 2013)

(untitled) - Makitalo, M.; Foi, A. (IEEE Trans. Image Process., 2013)

Probability theory. Graduate texts in mathematics - Loeve, M. (Springer, 1977)

(untitled) - Chang, S. G.; Yu, B.; Vetterli, M. (IEEE Trans. Image Process., 2000)

(untitled) - Stollnitz, E. J.; Derose, T. D.; Salesin, D. H. (IEEE Comput. Graphics Appl., 1995)

(untitled) - Wang, Z.; Bovik, A. C.; Sheikh, H. R.; Simoncelli, E. P. (IEEE Trans. Image Process., 2004)

Proceedings of the IEEE International Conference on Intelligent Robots and Systems - Yang, G.; Nelson, B. J. (Wavelet-based autofocusing and unsupervised segmentation of microscopic images, 27.10.2003-31.10.2003, 2003)

(untitled) - Pöselt, E.; Schmidtke, C.; Fischer, S.; Peldschus, K.; Salamon, J.; Kloust, H.; Tran, H.; Pietsch, A.; Heine, M.; Adam, G.; Schumacher, U.; Wagener, C.; et al. (ACS Nano, 2012)

(untitled) - Ostermann, J.; Merkl, J. P.; Flessau, S.; Wolter, C.; Kornowski, A.; Schmidtke, C.; Pietsch, A.; Kloust, H.; Feld, A.; Weller, H. (ACS Nano, 2013)

(untitled) - Schmidtke, C.; Pöselt, E.; Ostermann, J.; Pietsch, A.; Kloust, H.; Tran, H.; Schotten, T.; Bastús, N. G.; Eggers, R.; Weller, H. (Nanoscale, 2013)

(untitled) - Huang, S. H.; Heikal, A. A.; Webb, W. W. (Biophys. J., 2002)

(untitled) - Orzekowsky-Schroeder, R.; Klinger, A.; Martensen, B.; Blessenohl, M.; Gebert, A.; Vogel, A.; Hüttmann, G. (J. Biomed. Opt., 2011)